2021
DOI: 10.21601/jisem/10958
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Usage and Applications of Social Media Analytics

Abstract: This paper presents the report of a social media analytics (SMA) review. The review conducted to find out the methods and tools used in social media analytics, types of social media platforms which the SMA are performed and the field which SMA has been performed. Social media contains a lot of user uploaded data in different formats like text, images, photos, video etc. These large volumes of data are converted in meaningful information which can be understood using different methods and tools which are called… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 52 publications
(105 reference statements)
0
3
0
Order By: Relevance
“…Garg et al [104] found that social media analytics, by harvesting customers' engagement role, could significantly improve business performances and digital marketing outcomes. Social media analytics involve key components that allow business organizations to gather useful information regarding customers' segments and are also efficiently utilized for marketing business processes [105]. By modeling social media analytics, business marketers can gain insights for their digital marketing campaigns depending on their market characteristics [106].…”
Section: Discussionmentioning
confidence: 99%
“…Garg et al [104] found that social media analytics, by harvesting customers' engagement role, could significantly improve business performances and digital marketing outcomes. Social media analytics involve key components that allow business organizations to gather useful information regarding customers' segments and are also efficiently utilized for marketing business processes [105]. By modeling social media analytics, business marketers can gain insights for their digital marketing campaigns depending on their market characteristics [106].…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy incidents, such as the spread of rumors on social media leading to panic buying during the COVID-19 epidemic and the dissemination of misinformation triggering ethnic conflict, highlight the importance of understanding social media usage patterns in the current information age. While innovative researchers and business experts worldwide have been exploring new approaches for gathering, combining, and analyzing vast amounts of social media data [1][2], it remains unclear if similar studies have been conducted in the Sri Lankan setting. Therefore, this study aims to address this gap by offering a comprehensive review of social media research conducted in Sri Lanka, providing unique insights on the most popular sectors in which social media research has been conducted, prevalent data analytic techniques utilized in such studies, and social media platforms that have generated the most discussion among the research community.…”
Section: Introductionmentioning
confidence: 99%
“…Several literature reviews exist on social media applications, analytics, and their effects concerning various fields. Examples include systematic literature reviews that discuss techniques, software tools and platforms for social media analytics [1][2][5][6] and review articles that focus on domains such as education [7][8], health [9], politics [10], disaster management [11] and business and innovation [12]. Although there are several literature reviews on the data and usage of social media in different application fields, we could not locate any that discussed the general trends and applications of research on social media usage concerning a specific country.…”
Section: Introductionmentioning
confidence: 99%
“…18 The applications for social media analysis are seen in a variety of industries including healthcare, marketing, politics, sports, media, finance and agriculture. 19 It is commonly used to gain insights on population attitudes and behaviours as well as gain feedback for a particular product or service. 20,21 Studies have also demonstrated the predictive power of social media analysis which, for example, can be used to forecast public attendance of major events and predict election outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The applications for social media analysis are seen in a variety of industries including healthcare, marketing, politics, sports, media, finance and agriculture 19 . It is commonly used to gain insights on population attitudes and behaviours as well as gain feedback for a particular product or service 20,21 .…”
Section: Introductionmentioning
confidence: 99%